Analisis Penerapan Akuntansi Lingkungan sebagai Tolak Ukur dalam Optimalisasi Tanggung Jawab Sosial Pada PG Kebon Agung Malang - Manshur, Yusrotul Afiyah; Nawirah, Nawirah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This purpose of the researce to analyze of enviromental accounting and social responsibility, to improver the company performance by recording, classifying, summarizing and presenting the cost of social and environmental responsibility on the company's financial statements. This research was conducted at PG Kebon Agung Malang which one of the biggest sugar factory in Malang.This research is a kind of qualitative research, data obtained by doing observation, interview, documentation and observation in the field. As secondary and primary data source, the staff of PG Kebon Agung as internal party of company and surrounding community as external party.The results of this research is; firstly, in PG Kebon Agung Malang has implemented of environmental accounting practices by recording up to reporting social and environmental costs, but they are not suitable at the practice PG entry the cost of social responsibility into one in the income statement financial loss provite with other expense accounts; Secondly, the optimization of social responsibility for the conformity of the results of this study with PP RI. 47 of 2012 proved to be well implemented, with the certificate of analysis test, and the result of analysis there are three types of waste liquid waste, solid, and air have met the standard quality of waste specified by the East Java Governor's Regulation No 10/2009 with a percentage of expenses incurred of 1.9% of net profit for environmental costs and a 0.3% cost percentage of net income for social responsibility, indicating financial performance and obligations of PG Kebon Agung, as well as compliance with Government regulations implemented in a balanced manner, by exercising the rights and obligations of the company continuously.